IMPLIKATUR DALAM PEMBELAJARAN BAHASA INDONESIA DI SMA LABSCHOOL UNTAD PALU - Tokuasa, Mursalim (BAHASANTODEA, 2015)
Implikatur represents the form of language use of oral language or written language that represents different meaning intended by speaker. Teaching and Learning process at formal education is one of Ianguage activities that demand good communications between students and teachers. Implikatur in Indonesian study at SMA Labschool Untad Palu is one of Ianguage phenomenon that happened in formal education environment. Implikatur discourse happened because the influence from context factor when the discourse take place. This research carried 3 implikatur problems in Indonesian study at SMA Labschool Untad Palu, namely; (1) implikatur forms in Indonesian study at SMA Labschool Untad Palu; (2) implikatur funtions in Indonesian study at SMA Labschool Untad Palu; and (3) strategies of implikatur use in Indonesian study at SMA Labschool Untad Palu.Relevant with the problems, hence this research aim to describe the implikatur forms, functions, and strategies of implikatur use in Indonesian study at SMA Labschool Untad Palu. This Research represented the descriptive qualitative research by using the content analysis approach. The data of this research came from teachers and students’ discourse in teaching and learning process at SMA Labschool Untad Palu.The results of this research in the form of; (1) Implikatur forms, that are implikatur in the form of questions, implikatur in the form of statements, implikatur in the form of answers, and implikatur in the form of comands; (2) Implikatur functions, that are motivation function, humor function, draw attention function, violation prevention function, reference giving function, connection giving function; (3) Implikatur strategies, that are angry strategy indirectly, humorous indirectly, expected informations indirectly, and expected actions indirectly. Keywords: Implikatur, Indonesian Study, SMA Labschool Untad Palu.